Building new heritage for the future: investigating community architecture paradigms in contemporary architecture of Iran (1978–2020) - Kamelnia, Hamed; Hanachi, Pirouz (Journal of Architecture and Urbanism, 2022)
Contemporary Iranian architecture in the last forty decades has been influenced by different currents and trends, from modern trends to postmodern and kitsch and attention to regionalism in recent years. Yet, there have been fewer participatory approaches in design and especially community architecture. As an approach, participatory architecture has not been a suitable approach for many architects because they believe the user interference leads the project to a wrong path, and it is a time-consuming process. On the other side, some governments make seductive participation for some political aims. Many recourses in this field talk about the user’s direct participation in the design process, and also many of the cases are not outstanding in contemporary architecture literature. So just a seduce participation occurs during design. Some methods used in this kind are questionnaires, workshops, interviews, etc. Some cases consider involvement during the project’s construction phases (especially in developing countries). Assessing different successful Iranian projects in four recent decades shows a little kind of participatory methods in CA of Iran. The lack of usage of community architecture paradigms leads to not being too good architecture practices. Some projects with a successful appearance made community design principles in the design process. Combining regionalism and community design approaches make responsible and sustainable projects for the future. In this study, by using the PAR research method, the typology of participatory architecture in contemporary Iranian architecture has been analyzed. Seven typologies of participation in the design process show different levels and conditions of participation for users and architects. Some typologies such as interpretive and regional participation consider more values, costumes and user behaviors, and they are more indirect. In the next step, using the case study research method and qualitative analysis by the ATLAS.ti software, the relationship between the concepts of community architecture and its impact on the formation of Iranian architecture has been discussed. Different typologies of participation in architectural cases are wide ranges of successful methods of participation that if far from previous typical involvement consideration in social mobilization and questioner’s procedures. Today, questionnaire participation and social mobilization are named seduce participation (also, in some cases, may be useful). In recent years, the tendency towards participatory design with interpretive and regionalism approaches has increased. Studies show the use of three branches: 1 – Elements of traditional Iranian-Islamic architecture (29 codes), incorporation with the environment (23 codes), use of natural light (17 codes) are the most important reasons for the formation of today’s Iranian architecture. In recent years, by combining the concepts of community architecture (29 codes) with emphasis on identity (4 codes), transparency (4 codes), attention to user needs (3 codes), privacy, sense of belonging, sense of ownership, and sense of unity have become the main criterion of architectural formations. Today, assessing the contemporary architecture of Iran (recent decades) shows the usage of responsible typologies of participation in the design process have a good impact on the built environment, and it also improves the condition of life for user and respects values, culture, costumes, needs and ideas, literature survey and recommends a sustainable future. The most influential factors in contemporary Iranian architectural ideas in recent years include topics such as the Usage of Iranian-Islamic traditional elements, harmony with nature, and natural light. Combining Iranian-Islamic traditional architecture elements (such as courtyards, Koushk, etc.) with community design architectural concepts with solutions such as social spaces, flexibility, platform spaces, courtyards are the most important features of the formation of today’s architecture. Central courtyard, Eyvan, and the Persian garden have been the three main elements of today’s Iranian architecture.